Development of pre-conceptual ITER-type ICRF antenna design for DEMO. (22nd March 2021) - Bobkov, V.; Usoltceva, M.; Faugel, H.; Kostic, A.; Maggiora, R.; Milanesio, D.; Maquet, V.; Ochoukov, R.; Tierens, W.; Zeus, F.; Zhang, W.
Abstract: ICRF antenna development for DEMO for the pre-conceptual phase is carried out by merging the existing knowledge about multi-strap ITER, JET and ASDEX upgrade antennas. Many aspects are taken over and adapted to DEMO, including the mechanical design and RF performance optimization strategies. The minimization of ICRF-specific plasma-wall interactions is aimed at by optimizing the feeding power balance, a technique already proven in practice. Technological limits elaborated for the components of ITER ICRF system serve as a guideline in the current design process. Several distinctive aspects, like antenna mounting, integration with the neighboring components or adaptation for neutron environment, are tackled individually for DEMO.